Antioxidant efficacies of rutin and rutin esters in bulk oil and oil‐in‐water emulsion. Issue 4 (24th August 2016) - Lue, Bena‐Marie; Sørensen, Ann‐Dorit Moltke; Jacobsen, Charlotte; Guo, Zheng; Xu, Xuebing
Abstract : The use of flavonoids as antioxidants in food formulations is limited due to their solubility and thereby their localization in the food products. However, enzymatic alkylation of flavonoids with lipophilic moieties alters their lipophilicity and thereby partitioning within different phases in a food product. This study aimed to evaluate the antioxidative efficiency of two derivatives of rutin, namely rutin laurate (C12:0) and rutin palmitate (C16:0) compared with their parent compound rutin and with butylated hydroxytoluene (BHT). Their efficiency as antioxidants at two different concentrations (25 and 200 × 10 −6 m ) was assessed in bulk oil and in an o/w emulsion system without and with iron addition. All evaluated compounds revealed antioxidant effects. However, rutin and BHT were the most efficient antioxidants in bulk oil followed by rutin palmitate, whereas rutin laurate acted as either an antioxidant or a prooxidant at low and high concentrations (25 and 200 × 10 −6 m ), respectively. In emulsions, rutin and BHT in high concentration (200 × 10 −6 m ) were more efficient than rutin esters. Thus, alcylation of rutin with medium chain fatty acids did not improve the antioxidant ability, neither in bulk oil nor in o/w emulsion. Interestingly, rutin had stronger antioxidative effect than BHT upon iron addition to the emulsion. Practical application: According to the antioxidant hypothesis, the polar paradox, more amphiphilic antioxidants should perform as better antioxidants in emulsions than more polar antioxidants. The finding in this study revealed that lipophilization of rutin did not improve its antioxidant capacity in emulsions compared to untreated rutin. This stresses the importance of evaluating the antioxidant in each emulsion systems before selecting appropriate antioxidants for optimal protection against lipid oxidation. Lipid oxidation in bulk oil and o/w emulsion. Rutin and BHT more efficient antioxidants in bulk oil and emulsion than rutin ester. Acylation of rutin with C12 or C16 did not improve the antioxidant ability of rutin neither in bulk oil or emulsion. Abstract : Lipid oxidation in bulk oil and o/w emulsion. Rutin and BHT more efficient antioxidants in bulk oil and emulsion than rutin ester. Acylation of rutin with C12 or C16 did not improve the antioxidant ability of rutin neither in bulk oil or emulsion.